PELAKSANAAN PERJANJIAN PENGADAAN BARANG DAN JASA ANTARA CV.JOGJA KONVEKSI DAN DINAS SOSIAL PROVINSI SUMATERA - Effendi, Devirianti; Hamka, Jefry (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The procurement of goods and services for government purposes is one of the tools to drive economic growth in order to improve the national economy and enhance the welfare of the Indonesian people. This is because the procurement of goods and services, especially in the public sector, is closely related to the use of state budgets. The implementation of procurement agreements for goods and services is based on Article 1338 paragraph (1) of the Civil Code and Presidential Regulation No. 12 of 2021 concerning Amendments to Presidential Regulation No. 16 of 2018 on Government Procurement of Goods and Services.The problem formulation in this thesis includes: first, how is the implementation of the procurement agreement for goods and services between the Social Service Office of West Sumatra Province and CV. Jogja Konveksi? Second, what are the obstacles and efforts to resolve issues in the implementation of the procurement agreement between CV. Jogja Konveksi and the Social Service Office of West Sumatra Province?This research is a legal study with a descriptive specification, illustrating the implementation of the procurement agreement for goods and services between the Social Service Office of West Sumatra Province and CV. Jogja Konveksi. The research approach used is the normative juridical approach as the main approach, supported by an empirical juridical approach.Based on the research results and discussion, the following conclusions are drawn: first, in the implementation of the procurement agreement for goods and services between the Social Service Office of West Sumatra Province and CV. Jogja Konveksi, the goods and services provider is in a weak position, making them more likely to comply with the conditions set by the goods and services user. Second, obstacles in the implementation of the procurement agreement include errors in the electronic procurement system, which sometimes delays contracts, and vendors violating contract terms, causing issues. Efforts to address these obstacles include improving the electronic procurement system to prevent system errors and enhancing human resource quality by providing knowledge and socialization on contract breaches and the consequences of violating contract terms.Keywords: Agreement, Contract, Procurement of Goods and Services.